2005
DOI: 10.1111/j.1540-8159.2005.09481.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Energy Sources for the Ablation of Arrhythmias

Abstract: IntroductionAs catheter-based ablative therapies of cardiac arrhythmias become standard of care, establishing and refining the tools used for these procedures has become critical. With a wide variety of energy sources now available for use in arrhythmia ablation, understanding advantages, disadvantages, and specific uses of each modality can help physicians choose the best modality to achieve a successful result. This article reviews many of the energy sources currently available and discusses each modality's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 50 publications
0
22
0
3
Order By: Relevance
“…Radiofrequency current is the most commonly used energy source for SVT ablation (80). Cryoablation is used as an alternative to radiofrequency ablation to minimize injury to the AV node during ablation of specific arrhythmias, such as AVNRT, para-Hisian AT, and para-Hisian accessory pathways, particularly in specific patient populations, such as children and young adults.…”
Section: Basic Principles Of Electrophysiological Study Mapping Andmentioning
confidence: 99%
“…Radiofrequency current is the most commonly used energy source for SVT ablation (80). Cryoablation is used as an alternative to radiofrequency ablation to minimize injury to the AV node during ablation of specific arrhythmias, such as AVNRT, para-Hisian AT, and para-Hisian accessory pathways, particularly in specific patient populations, such as children and young adults.…”
Section: Basic Principles Of Electrophysiological Study Mapping Andmentioning
confidence: 99%
“…The scope of this summary discusses the various lesion sets that have been used in the surgical treatment of atrial fibrillation. A detailed discussion of all of the technologies is beyond the scope of this review and can be found elsewhere [13,[15][16][17][18].…”
Section: Opinion Statementmentioning
confidence: 99%
“…Obwohl das Risiko einer PV-Stenose ebenso wie die Entwicklung anderer, z. B. embolischer Ablationskomplikationen vornehmlich auf die Verwendung von Radiofrequenzenergie zurückzuführen ist, wird dieses Verfahren aufgrund der selteneren Flimmerrezidive gegenüber alternativen Methoden wie der Kryoablation aktuell noch bevorzugt eingesetzt [45]. Die hier gezeigte signifikante Reduktion der Anzahl der für eine komplette ostioatriale Leitungsblockade notwendigen Impulsapplikationen kann als Indikator für eine Effizienzsteigerung der Einzelablation interpretiert werden, die infolge einer verbesserten Katheterposition und einer gesteigerten Kontrolle der Stromabgabe auf eine erhçhte Sicherheit der CT-assistierten PVI hoffen lässt.…”
Section: Herz 1269unclassified